SOLENOPSIS (HYMENOPTERA, FORMICIDAE) FIRE ANT REACTIONS TO ATTACKS OF PSEUDACTERON FLIES (DIPTERA, PHORIDAE) IN SOUTHEASTERN BRAZIL - Porter, S. D.; Vandermeer, R. K.; Pesquero, M. A.; Campiolo, S.; Fowler, H. G. (Amer Entomol Soc, 1995)
We studied the responses of Solenopsis fire ants to Pseudacteon phorid fly attacks in southeastern Brazil. The presence of these phorid parasites triggered a suite of phorid-specific defense responses including reduced foraging, bait guarding, a curled defensive posture, and general colony immobility. The existence of these phorid-specific defenses indicates that Pseudacteon phorids exert substantial evolutionary pressure on South American fire ant populations.
Keywords: SOLENOPSIS INVICTA; SOLENOPSIS SAEVISSIMA; BIOLOGICAL CONTROL; DEFENSE RESPONSES; PARASITIC FLIES; BRAZIL